Pengaruh Ronde Keperawatan terhadap Tingkat Kepuasan Kerja Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Umum Aisyiyah Kudus - Tri Suwarto; Yulisetyaningrum Yulisetyaningrum; Indanah Indanah (Indonesian Journal of Nursing Research (IJNR), 2022)
This study aims to examine the effect of nursing rounds on nurse job satisfaction in the inpatient room of  Aisyiyah Hospital  Kudus. Design used in this study was quasi experimental with pretest posttest with control group design, a sample of 60 people. Determination of the sample using purposive sampling. The instruments used in this study were questionnaires. The results showed no significant effect of nursing rounds on nurse job satisfaction levels in the implementation of hospitalization (p = 0.004,alpha = 0.05), with professionalstatus subvariabel increased significantly after the  nursing rounds (p = 0.03 ,alpha=0.05). Nursing rounds is a viable strategy used to enhance nurse job satisfaction is based on professional status, autonomy, task requirements, and interaction